CORRELATION BETWEEN NUTRITIONAL STATUS AND THE OCCURRENCE OF PULMONARY TUBERCULOSIS IN CHILDREN - rahmadani, elsi; Fahriani, Metha; Sari, Gita Maya (Jurnal Kesehatan Saintika Meditory, 2023)
Pulmonary tuberculosis (TB) is still a public health problem in the world. This study aims to determine the correlation between nutritional status and the occurrence of pulmonary tuberculosis in children in the pulmonary polyclinic at Bengkulu Hospital. The method used is an analytical research design with a cross sectional approach. The sample in this study amounted to 31 children using a total sampling technique. This study uses SPSS with a chi-square bivariate statistical test with a value of = <0.05. The results of the univariate analysis showed that more than half of the 54.8% respondents or 17 respondents had good nutritional status, and more than half of the 71.0% respondents or 22 respondents did not have tuberculosis in children. There is a correltion between nutritional status and the occurrence of pulmonary tuberculosis in children. Researchers suggest the hospital to be more active in providing counseling or education about tuberculosis in children. Keywords: Nutritional Status, Pulmonary Tuberculosis, Children